Republic of Tajikistan : Poverty Reduction Strategy Paper; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2009)
This Joint Staff Advisory Note on the Republic of Tajikistan's Poverty Reduction Strategy Paper discusses economic development and policies. The authorities are working on enhancing Tajikistan's investment climate through a range of measures, including through eliminating unnecessary licenses and inspections, cutting the number of mandatory standards and easing certification procedures, strengthening property rights, and improving infrastructural services. Reforming the management of Barki Tajik and ensuring the transparency and accountability of operations are critical.